Photosynthetic apparatus efficiency of Sida hermaphrodita cultivated on heavy metals contaminated arable land under various fertilization regimes = Wydajność aparatu fotosyntetycznego Sida hermaphrodita uprawianego na glebie zanieczyszczonej metalami ciężkimi w warunkach zróżnicowanego nawożenia - Rusinowski, Szymon; Krzyżak, Jacek; Pogrzeba, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Contaminated and marginal lands are favourable place for biomass feedstock establishment, especially due to European Union directive 2009/28/EC. This strategy not only cover local demand for energy and heat but also can be valuable in those land phytomanagment. The second-generation perennial energy crop species are the most feasible for such purpose.
Keywords: energy plants; heavy metals; photosynthesis; chlorophyll fluorescence; senescence; rośliny energetyczne; metale ciężkie; fotosynteza; fluorescencja chlorofilu; starzenie